Accomplishment Motivation and Soft Skill Related to Learning Achievement - Diarni Junita; Suarman Suarman; Sri Kartikowati (Universitas Riau, 2018)
This study aims to determine the influence of achievement motivation through the role of soft skills to the learning achievement. This research was conducted due to the low achievement motivation of students at Economic Education Program Study, University of Riau. A total of 185 samples were selected from 344 number of population using Yamane statistical sampling technique. Data was collected by questionnaire and documentation techniques. It was then analyzed using path analysis. The results showed that Soft Skill played a positive role mediate that influence of accomplishment motivation on learning achievement. This means that learning achievement is not influenced by achievement motivation alone, but also supported by soft skill as intervening variable. In order to achieve achievement motivation students should have a successful future oriented attitude. Meanwhile, to improve soft skill students must have the ability to communicate, adapt and build relationships obtained from the ability of ICT and foreign languages.